TELEVISION AUDIENCE MEASUREMENT & APPLYING ON ADVERTISING ACTIVITY IN VIETNAM - Nguyen, Van Hung (Khoa Quốc tế, ĐHQGHN, 2019)
Television Audience Measurement is a popular field of study in the world but quite new for the Vietnam. The objective of the research is introduce a new and effective approach to the study of television audience to help advertiser/media agency/broadcaster understand the audience characteristics, habits, tastes… from which they can build and develop the effective and optimal communications strategies.